New Drugs for NASH and HIV Infection: Great Expectations for a Great Need. Issue 5 (29th April 2020) - Guaraldi, Giovanni; Maurice, James B.; Marzolini, Catia; Monteith, Kenneth; Milic, Jovana; Tsochatzis, Emmanuel; Bhagani, Sanjay; Morse, Caryn G.; Price, Jennifer C.; Ingiliz, Patrick; Lemoine, Maud; Sebastiani, Giada; et al.
Abstract : In recent years, there has been an increasing number of clinical trials for the treatment of nonalcoholic steatohepatitis (NASH). People living with human immunodeficiency virus (PLWH) are commonly excluded from these studies, usually due to concerns over drug–drug interactions associated with antiretroviral therapy. The Steatohepatitis in HIV Emerging Research Network, a group of international experts in hepatology and infectious diseases, discusses our current understanding on the interaction between human immunodeficiency virus and NASH, and the issues related to the inclusion of PLWH in NASH clinical trials. Recent trials addressing NASH treatment in PLWH are discussed. The risk of drug–drug interactions between antiretroviral therapy and aramchol, cenicriviroc, elafibranor, obeticholic acid and resmetirom (MGL‐3196), which are currently in phase 3 trials for the treatment of NASH, are reviewed. A model for trial design to include PLWH is proposed, strongly advocating for the scientific community to include this group as a subpopulation within studies.